Novel Green Biomimetic Approach for Synthesis of ZnO-Ag Nanocomposite; Antimicrobial Activity against Food-borne Pathogen, Biocompatibility and Solar Photocatalysis - Zare, M. (Nature Publishing Group, 2021)
10.1038/s41598-019-44309-w